Apoplastomes of contrasting cacao genotypes to witches’ broom disease reveals differential accumulation of PR proteins - De Oliveira, Ivina Barbosa; Alves, Saline dos Santos; Ferreira, Monaliza Macêdo; Santos, Ariana Silva; Farias, Keilane Silva; Assis, Elza Thaynara Cardoso de Menezes; Mora-Ocampo, Irma Yuliana; Muñoz, Jonathan Javier Mucherino; Costa, Eduardo Almeida; Gramacho, Karina Peres; Pirovani, Carlos Priminho (Frontiers in Plant Science, 2024)
Witches' broom disease (WBD) affects cocoa trees (Theobroma cacao L.) and is caused by the fungus Moniliophthora perniciosa that grows in the apoplast in its biotrophic phase and later progresses into the tissues causing serious losses in the production of cocoa beans. Therefore, the apoplast of T. cacao can provide important defense responses during the interaction with M. perniciosa. In this work, evaluated the protein profile of the apoplast of the T. cacao genotypes Catongo, susceptible to WBD, and CCN-51, resistant.The leaves of T. cacao were collected from asymptomatic plants grown in a greenhouse (GH) and from green witches' brooms grown under field conditions (FD) for extraction of apoplastic washing fluid (AWF). A total of 14 proteins were identified in Catongo GH and six in Catongo FD, with two proteins were in common, one up-accumulated and one down-accumulated. In CCN-51, 19 proteins were identified in the GH condition and 13 in FD, with seven proteins in common, one up-accumulated and six down-accumulated.Most proteins are related to defense and stress in both genotypes, with emphasis on Pathogenesis-Related Proteins (PR): PR-2 (β-1,3-glucanases), PR-3 and PR-4 (chitinases), PR-5 (thaumatine), PR-9 (peroxidases) and PR-14 (lipid transfer proteins). Furthermore, proteins from microorganisms were detected in the AWF. The enzymatic activities of PR-3 showed a significant increase (p<0.05) in Catongo GH and PR-2 activity (p<0.01) in CCN-51 FD. The protein profile of the T. cacao apoplastome offers insight into the defense dynamics that occur in the interaction with the fungus M. perniciosa and offers new insights in exploring future WBD control strategies.